Pemphigus vulgaris in a pregnant woman and her neonate - Ibrahim, Sameera Begum Kader (BMJ Publishing Group, 2012)
A 23-year-old pregnant woman in her second trimester of pregnancy presented with blisters on the face, abdomen and the leg. Based on the clinical presentation and skin biopsy (histopathology and direct immunofluorescence) the diagnosis of pemphigus vulgaris was established. The child born to this patient also had similar skin lesions. The lesions in the mother and the child improved after treatment. The authors report a rare case of pemphigus vulgaris in a pregnant lady and neonatal pemphigus in her child, both of whom were treated successfully.